A Mathematical Model of the Transmission Dynamics of Tuberculosis with Exogenous Reinfection in the Infection-Free State. Issue 2 (September 2022) - Pérez-Núñez, Jhelly-Reynaluz; Pino-Romero, Neisser; Vásquez-Serpa, Luis-Javier; Haya-Enríquez, Erwin-Fernando; Bravo-Orellana, Miriam
No abstract available